Using embedded instruments to design weblabs - Costa, Ricardo (2015)
The existence of digital instruments able to be remotely accessed justifies the appearance of weblabs in engineering education. Currently, weblabs adopt digital standalone and/or modular instruments to enable the conduction of remote experiments. Although, the evolution of digital processing techniques and the dissemination of reconfigurable devices, such as FPGAs, can be seen as an opportunity to reduce costs and to increase the flexibility in the design of digital instruments and, therefore, in the development of weblabs’ infrastructures. This paper explores the use of other type of digital instruments to create weblabs, named embedded instruments. It starts contextualizing those instruments, and suggests some architectures for their adoption in weblabs’ infrastructures. Latter, it points out the importance of following the IEEE1451.0 Std. to design embedded instruments able to be reconfigured in FPGAs, which can be the main elements of a reconfigurable weblab infrastructure. An example of an embedded oscilloscope implemented in a FPGA and described according to an architecture based on the IEEE1451.0 Std. finishes the paper.